ANALISIS RASIO KEUANGAN MENGGUNAKAN TIME SERIES DAN CROSS SECTION UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN - Wediyanto, Eko; Ariska, Fitriani (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The purpose of this study was to analyze the financial ratios of manufacturing companies listed on the IDX for the 2019-2023 period using financial ratio analysis, namely liquidity ratios, profitability ratios and activity ratios to assess the company's financial performance. The type of research used by researchers is descriptive quantitative using time series and cross sections, the data used in this research is secondary data, the results of the research show the average value of liquidity ratio PT. Gudang Garam Tbk. has the highest average current ratio and quick ratio values, while the highest average cash ratio is at PT. HM Sampoerna Tbk. The highest average value of activity ratio and profitability ratio of the three companies, namely PT. Gudang Garam Tbk. and PT. Bentoel International Investama Tbk. are PT. HM Sampoerna Tbk., this shows that the ability of PT. HM Sampoerna Tbk. more efficient in daily activities and the profits obtained within a period of 5 years (2019-2023) are more effective than PT. Gudang Garam Tbk and PT. Bentoel International Investama Tbk.